Finding the right words : Isidore's Synonyma in Anglo-Saxon England - Di Sciacca, Claudia (Toronto Old English series., 2008)
Isidore of Seville (circa 570-636) was the author of the Etymologiae,. the most celebrated and widely circulated encyclopaedia of the western Middle Ages. In addition, Isidore's Synonyma were very successful and became one of the classics of medieval spirituality. Indeed, it was the Synonyma that were to define the so-called 'Isidorian style,' a rhymed, rhythmic prose that proved influential throughout the Middle Ages.Finding the Right Words is the first book-length study to deal with the transmission and reception of works by Isidore of Seville in Anglo-Saxon England, with a particular focus on the Synonyma. Beginning with a general survey of Isidore's life and activity as a bishop in early seventh-century Visigothic Spain, Claudia Di Sciacca offers a comprehensive introduction to the Synonyma, drawing special attention to their distinctive style. She goes on to discuss the transmission of the text to early medieval England and its 'vernacularisation,' that is, its translations and adaptations in Old English prose and verse. The case for the particular receptiveness of the Synonyma in Anglo-Saxon England is strongly supported by both a close reading of primary sources and an extensive selection of secondary literature. This rigorous, well-documented volume demonstrates the significance of the Synonyma to our understanding of the literary pretensions and pedagogical practices of Anglo-Saxon England, and offers new insights into the interaction of Latin and vernacular within its literary culture.